Carotenoid in ulam species as alternative food intervention to combat the aftermath of the COVID-19 infection - Mohd Hatta, Farah Ayuni; Mat Ali, Qurratu Aini; Othman, Rashidi; Ramya, Razanah; Wan Sulaiman, Wan Syibrah Hanisah; Mohd Latiff, Nur Hanie (Penerbit Universiti Kebangsaan Malaysia, 2025)
The COVID-19 pandemic has been declared an urgent public health issue affecting every country worldwide. People often inquire about viable COVID-19 infection seickness treatment. However the nation has yet to discover the best treatment for this disease. Hence, finding the initiative focusing on a single active component to combat the COVID-19 pandemic aftermath is critical. The food and pharmaceutical industries have proposed potential treatment to enhanced the body immune system before and after exposure COVID-19 and a daily supplement. We must eat healthy food daily to improve our body health and resilience. A balanced diet, as well as vegetables and fruits, should be included in a daily meal.